Hubungan Minat Belajar Daring dengan Hasil Belajar Kognitif Siswa Pembelajaran Biologi di SMP Swasta Muhammadiyyah 1 Medan - Pakpahan, Enni Halimatussa’diyah; Hartono, Adi; Adisti, Yuda; Munthe, Dea Wahdania (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to evaluate the relationship between online learning interest and students' cognitive learning outcomes during online Biology learning at Muhammadiyah 1 Medan Private Junior High School. Observations show that online learning interest and learning outcomes are still relatively low, so an evaluation of online learning is needed. This research uses quantitative methods and the data analysis used is the product moment correlation data analysis to determine the positive relationship between online learning interest and students' cognitive learning outcomes during the online learning process at Muhammadiyah 1 Medan Private Junior High School.